Optimalisasi Literasi Teknologi dan Kreativitas Siswa Melalui Program Kampus Mengajar di SD IT Ibnu Abbas Lampung - Ammalia, Afifah; Azizah, Alif Luthvi; Wasim, Arif Al; Khoiri, Ahmad; Mutmainah, Kurniawati; Khanifa, Nurma Khusna (Yayasan Inspirasi El Burhani, 2025)
Introduction: Primary education plays an important role in shaping students' character, literacy, and skills. However, limited literacy facilities, technological skills, and spaces for creative expression remain challenges at SD IT Ibnu Abbas Lampung. Objective: The purpose of this service was to optimize student literacy, basic technology skills, creativity, and discipline at SD IT Ibnu Abbas through the Kampus Mengajar program while maintaining the school's Islamic values. Method: This community service was carried out from February to June 2024 through collaborative activities, including creating reading corners, literacy training, basic computer and Canva workshops, interactive numeracy sessions, creative classroom projects, and environmental literacy programs. The participants were students in grades 5 and 6, teachers, and the broader school community. Result: The program successfully established a functional reading corner with 73 books, improved student literacy through storytelling activities, introduced basic computer and Canva skills, revitalized classroom bulletin boards with student creations, developed a multilingual educational garden, enhanced numeracy understanding through interactive media, and fostered entrepreneurial skills through student projects. Students showed increased confidence, creativity, and digital literacy. Conclusion: The Kampus Mengajar program made a significant contribution to improving literacy, technology, and student creativity at SD IT Ibnu Abbas Lampung while remaining aligned with the school's mission of Islamic character development. Sustainable collaboration between students, teachers, and the Kampus Mengajar team is crucial for long-term improvements in educational quality.